2020
DOI: 10.1093/hropen/hoaa046
|View full text |Cite
|
Sign up to set email alerts
|

In vitro activation of ovarian cortex and autologous transplantation: A novel approach to primary ovarian insufficiency and diminished ovarian reserve

Abstract: BACKGROUND Primary ovarian insufficiency (POI) and diminished ovarian reserve are two conditions that affect women’s fertility. Oocyte donation remains an option for these patients; however, the development of certain novel technologies, such as in vitro activation of ovarian cortex (IVA), enables the possibility of activating the pool of resting primordial follicles, increasing the chance of pregnancy. OBJECTIVE AND RATIONALE Here, we review … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 67 publications
1
11
0
Order By: Relevance
“…After 2018, there was a shift from hormone replacement therapy to more innovative treatment strategies. In vitro activation (IVA) of the ovarian cortex combined with autologous transplantation is one of the novel approaches to primary ovarian insufficiency and diminished ovarian reserve [ 40 ]. Later, a simplification of the technique designated “Drug-Free IVA” has shown encouraging results in patients with POI [ 41 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…After 2018, there was a shift from hormone replacement therapy to more innovative treatment strategies. In vitro activation (IVA) of the ovarian cortex combined with autologous transplantation is one of the novel approaches to primary ovarian insufficiency and diminished ovarian reserve [ 40 ]. Later, a simplification of the technique designated “Drug-Free IVA” has shown encouraging results in patients with POI [ 41 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, they represent a finite source of ovarian follicles and their recruitment is an indispensable step as it determines reproductive lifespan [ 23 , 24 ]. The activation of EFs is modulated strictly to ensure only a small number of PFs can be activated [ 10 , 25 ]. Subsequently, they undergo continuous folliculogenesis to develop to later stages of development until the ovulation occurs.…”
Section: The Activation Of the Efs In Vitromentioning
confidence: 99%
“…The development of EFs is a complicated process governed by a number of signaling pathways and components [ 25 , 95 , 96 ]. Recent computational studies revealed that these components interact in different ways to promote the transition from PFs to the primary stage [ 83 ].…”
Section: Other Regulatory Components Stimulating the Efs’ Developmmentioning
confidence: 99%
See 1 more Smart Citation
“…They specifically rejected ovarian tissue cryopreservation for this indication. Some authors propose this ovarian tissue cryopreservation with the aim of in vitro activation of ovarian cortex before autologous transplantation [25]. However, this innovative method must be interpreted cautiously and deserves further well-conducted studies.…”
Section: Idiopathic Diminished Ovarian Reserve In the Absence Of Gynecologic And Endocrinologic Diseasesmentioning
confidence: 99%